Higher temperatures and lower osmotic potentials negatively impact Rhipsalis Gaertn. (Rhipsalideae, Cactaceae) germination and seedling survival - Gonçalo, Rafael Reis [UNESP]; de Souza Palma, Renan Marcelo [UNESP]; Gonzaga, Diego Rafael; de Almeida, Odair José Garcia [UNESP]; Kolb, Rosana Marta [UNESP] (Springer Nature, 2025)
Understanding how seeds and seedlings respond to key environmental factors, such as substrate moisture and temperature, is crucial for advancing insights into the ecophysiology of epiphytic plants during their establishment and their ability to adapt to a changing climate. We investigated seed germination, germination recovery, and seedling survival of eight species of Rhipsalis Gaertn. (Cactaceae), a widely distributed but threatened genus of epiphytic cacti native to Brazil. Tests were performed at five temperatures (15, 20, 25, 30, and 35 °C), six osmotic potentials (0, -0.2, -0.4, -0.6, -0.8, and − 1.0 MPa), and after osmotic and temperature stress alleviation (recovery treatment at 0 MPa and 25 °C). Optimal germination was obtained between 20 and 25 °C under no water deficit. In contrast, germination under negative osmotic potential treatments and elevated temperatures was lower, unsynchronized, and slower. High temperatures and pronounced water deficit inhibited germination and promoted seedling mortality. Most species achieved germination greater than 50% during recovery, but stronger or total inhibition was observed in specific cases. However, most seeds that did not germinate were viable (alive) at the end of all experiments. Our results indicate that Rhipsalis seeds can tolerate unfavorable conditions by spreading or inhibiting germination. Nevertheless, extended heat and drought events predicted in the following decades could alter environmental cues and decrease seedling survival, suggesting that the establishment of new individuals might be impaired if such conditions are confirmed in the future.